Indoor environment quality: a new challenge for environmental education. (27th June 2005) - Ramos, J.E.; Pitarma, R.A.; Ferreira, M.E.; Carvalho, M.G.
Presently, most people are aware that pollution of the external air (atmospheric pollution) is prejudicial to health, but few know that the indoor environment can also have highly noxious effects in human beings. In certain cases indoor pollution even can reach levels higher than about ten times that of external pollution. All over the world there are more and more frequent unpleasant manifestations in relation to indoor Lisboa Codex environment quality. This domain is a new challenge for environmental education, which has a fundamental role in the increment of the quality of life. The main objective of this paper is the relationship among the different environmental parameters, the occupational health and the variety of sensations and states of mind in which satisfaction with the indoor environment is expressed. They are referred to as the several causes of an inadequate indoor environment.